2012
DOI: 10.1113/jphysiol.2012.228247
|View full text |Cite
|
Sign up to set email alerts
|

Heterosynaptic plasticity induced by intracellular tetanization in layer 2/3 pyramidal neurons in rat auditory cortex

Abstract: Key points summary• Learning systems equipped with Hebbian-type associative plasticity are prone to runaway dynamics of synaptic weights and lack mechanisms for synaptic competition; these problems can be resolved by heterosynaptic plasticity: changes at synapses which were not active during the induction.• We show that in layer 2/3 pyramidal neurons from auditory cortex a purely postsynaptic challenge, intracellular tetanization, can induce heterosynaptic plasticity; similar to visual cortex, plasticity direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…Disruption of NO signaling in intracellular tetanization experiments did not completely abolish presynaptic changes, implying involvement of additional retrograde signaling systems (Lee and others 2012; Volgushev and others 2000). Activation of metabotropic glutamate receptors (mGluRs) can trigger the production, release, and retrograde action of endocannabinoids, including heterosynaptic LTD at inhibitory synapses (Chevaleyre and Castillo 2003; Chevaleyre and others 2006; Chiu and others 2010; Maejima and others 2001; Pan and others 2008).…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 90%
See 3 more Smart Citations
“…Disruption of NO signaling in intracellular tetanization experiments did not completely abolish presynaptic changes, implying involvement of additional retrograde signaling systems (Lee and others 2012; Volgushev and others 2000). Activation of metabotropic glutamate receptors (mGluRs) can trigger the production, release, and retrograde action of endocannabinoids, including heterosynaptic LTD at inhibitory synapses (Chevaleyre and Castillo 2003; Chevaleyre and others 2006; Chiu and others 2010; Maejima and others 2001; Pan and others 2008).…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 90%
“…Indeed, the rise of [Ca 2+ ] in is sufficient to induce plasticity (Neveu and Zucker 1996; Yang and others 1999). Induction of long-term heterosynaptic plasticity by intracellular tetanization and other protocols was impaired or blocked by chelation of intracellular calcium with EGTA (Arami and others 2013; Bright and Brickley 2008; Han and Heinemann 2013; Lee and others 2012; Nugent and others 2007). Substantial rise of [Ca 2+ ] in is produced by bursts of back-propagating action potentials activating voltage-dependent calcium channels (Miyakawa and others 1992; Petrozzino and Connor 1994; Schiller and others 1995; Schiller and others 1998; Yuste and Denk 1995), and can be further amplified by calcium release from internal stores (Berridge 1998; Fagni and others 2000; Nakamura and others 1999).…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 99%
See 2 more Smart Citations
“…It was originally thought that the unstimulated inputs that become weaker do so in the absence of synaptic input, but a careful study of heterosynaptic LTD in the dentate gyrus, the hippocampal region where heterosynaptic LTD has been most successfully studied, showed that spontaneous presynaptic activity is, in fact, required [38]. By contrast, a study of LTD in layer 2/3 pyramidal cells induced heterosynaptic LTD in the slice, where spontaneous input is unlikely [39]. The authors argued that this form of LTD has a role in preventing runaway synaptic modifications in the network and thus may be a form of homeostatic control [40].…”
Section: (D) Long-term Depressionmentioning
confidence: 99%